2006
DOI: 10.1680/macr.2006.58.6.367
|View full text |Cite
|
Sign up to set email alerts
|

Strain of heated concrete during two thermal cycles. Part 1: strain over two cycles, during first heating and at subsequent constant temperature

Abstract: This paper presents the strain behaviour of three nuclear reactor type plain unsealed (50–60 N/mm2) concretes exposed under 0% and 20% compressive loads to a 14-day two-thermal-cycle test (test temperatures ranging from 100°C to 600°C). A generic approach is taken for wider application and for the in-depth understanding of the behaviour of heated concrete in general. Concrete during the two thermal cycles experiences both expansive and contractive strains. The former includes ‘thermal expansion’, cracking expa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 17 publications
1
34
0
1
Order By: Relevance
“…For practical purposes, transient creep can be described accurately enough by concrete overall behavior. In this case, the concept of LITS (Load Induced Thermal Strain) defined in [64], can be adopted. It includes both transient creep and mechanical strain components (plastic strains and changes in the elastic strain due to concrete softening behavior).…”
Section: Transient Creepmentioning
confidence: 99%
“…For practical purposes, transient creep can be described accurately enough by concrete overall behavior. In this case, the concept of LITS (Load Induced Thermal Strain) defined in [64], can be adopted. It includes both transient creep and mechanical strain components (plastic strains and changes in the elastic strain due to concrete softening behavior).…”
Section: Transient Creepmentioning
confidence: 99%
“…It appears during the non-stationary heating of concrete under sustained mechanical load [5,[33][34][35][36][37]. It was shown that the presence of this phenomenon could relax the compressive stresses in a column subjected to temperature [39,40] and that this strain component can reach a high magnitude.…”
Section: Transient Thermal Strain Of Concretementioning
confidence: 99%
“…It was shown that the presence of this phenomenon could relax the compressive stresses in a column subjected to temperature [39,40] and that this strain component can reach a high magnitude. Extensive studies of this phenomenon have been conducted for ordinary concretes by [35][36][37][38]. More recent studies have been carried out, principally for HPC, in order to assess and understand contributing mechanisms of transient thermal strain activation.…”
Section: Transient Thermal Strain Of Concretementioning
confidence: 99%
“…LITS master curve acc. to Khoury [3] In general, it is found that LITS depends strongly on the level of the applied compressive stress. Unlike free thermal strain, LITS is not reversible upon cooling and occurs only during the initial heating.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the compressive stress on thermal strain was first observed in the 1960-ies and has been vastly investigated since [1,2,[4][5][6][7]. Khoury [3][4][5] performed several experimental studies, where most of the relevant parameters such as load level, aggregate type, degree of saturation etc. were varied.…”
Section: Introductionmentioning
confidence: 99%